2017
DOI: 10.1039/c7nr05336c
|View full text |Cite
|
Sign up to set email alerts
|

Extreme tuning of wetting on 1D nanostructures: from a superhydrophilic to a perfect hydrophobic surface

Abstract: The tuning of wetting over an extreme range, from superhydrophilic to superhydrophobic, was demonstrated on 1D Al/AlO nanostructures. While chaotic and tangled 1D Al/AlO nanostructures exhibited complete wetting, they became water repellent (with a water contact angle (CA) ≥173°) after the infiltration of poly[bis(2,2,2-trifluoroethoxy)phosphazene] (PTFEP) solution. This simple strategy allows the achievement of two extreme wetting regimes, perfect wetting and non-wetting, without altering the nanostructured s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The dependence of WCA on surface morphology at the nanoscale is also under active investigation. [83][84][85] Finally, it was reported that the wettability of the calcite/oil/brine system depends on a variety of factors such as brine concentration 86 and temperature. 87 It has been proposed that ions present in seawater altering the surface charge of calcite is responsible for wettability alteration.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of WCA on surface morphology at the nanoscale is also under active investigation. [83][84][85] Finally, it was reported that the wettability of the calcite/oil/brine system depends on a variety of factors such as brine concentration 86 and temperature. 87 It has been proposed that ions present in seawater altering the surface charge of calcite is responsible for wettability alteration.…”
Section: Discussionmentioning
confidence: 99%
“…The arrows in Figure b show nanospheres assembled on silanized HNT particles which create rough surfaces, a characteristic critical to enhancing the hydrophobicity. These nanospheres create the needed air gaps that reduce the solid–liquid interaction . The highly irregular shape of Si–HNT particles is helpful in creating surface roughness on the cotton fibers which increases the WCA …”
Section: Resultsmentioning
confidence: 99%
“…These nanospheres create the needed air gaps that reduce the solid-liquid interaction. [37] The highly irregular shape of Si-HNT particles is helpful in creating surface roughness on the cotton fibers which increases the WCA. [38] Figure 3 shows TEM images of Si-HNT particles at different magnifications.…”
Section: Figure 1amentioning
confidence: 99%
See 1 more Smart Citation
“…Determining CAs exceeding 160°–170° (especially when water droplets do not come to rest on a horizontal surface) by using conventional static analysis is not trivial. Recently we presented an alternative approach by recording a videotape during compressing a water droplet attached to a relatively hydrophobic surface with a counter superhydrophobic (to be tested) surface . This method is known as the contact–compress–release technique .…”
mentioning
confidence: 99%